On Bernstein-Type Theorems in Semi-Riemannian Warped Products - Wenjie Wang; Ximin Liu (Advances in Mathematical Physics)
Complete spacelike hypersurfaces immersed in semi-Riemannian warped products are investigated. By using a technique according to Yau (1976) and a reasonable restriction on the mean curvature of the hypersurfaces, we obtain some new Bernstein-type theorems which extend some known results proved by Camargo et al. (2011) and Colares and Lima (2012).